CRA's 25th anniversary: the past, present, and future - Kenneth H. Thomas (Levy Economics Institute of Bard College, 2002)
This paper focuses on the past, present, and future rules and regulations implementing CRA as developed, applied, and enforced by the federal bank and thrift regulators. The past rules and regulations refer to those in effect during the law's first 18 years, through 1995, when CRA underwent its first major reform. The present CRA rules and regulations were adopted then, with the mandate that they would be reviewed for possible reform in 2002. The future rules and regulations are being drafted now by the regulators, based on their review of approximately 400 public comments; the reform recommendations should be released sometime during the second half of 2002. The future of CRA's legacy as arguably the perfect fair market regulation in a world of Compassionate Capitalism will depend upon the direction of these reforms. Optimal public policy by the bank and thrift regulators in this regard must represent the ideal balance between competing consumer and industry interests. This paper represents the first comprehensive analysis of the public comments and concludes with specific recommendations that will lead to optimal public policy.
Keywords: 330